2012
DOI: 10.1080/17550874.2012.667841
|View full text |Cite
|
Sign up to set email alerts
|

Water loss from flower heads predicts seed release in two invasive thistles

Abstract: Background: Non-random seed release caused by plant responses to weather conditions is important for seed dispersal. Much is known about the effects of wind speed and turbulence, but our understanding of the effects of water loss on seed release is either qualitative, or indirect and phenomenological. Aims: To quantify the empirical relationship between water loss and seed release. Methods: Capitula of the invasive thistles Carduus acanthoides and C. nutans were collected from the field and treated for either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 44 publications
4
21
0
Order By: Relevance
“…; Greene & Quesada ; Marchetto et al . ). Hence, the cumulated stress in the abscission zone would be reduced during these periods, delaying diaspore abscission.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Greene & Quesada ; Marchetto et al . ). Hence, the cumulated stress in the abscission zone would be reduced during these periods, delaying diaspore abscission.…”
Section: Discussionmentioning
confidence: 97%
“…For example, diaspore abscission could be conditional not only to wind speed but also to relative humidity through the use of empirical functions estimated in experimental studies (Marchetto et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Marchetto et al . ) or capsule design (Kadereit & Leins ) may affect seed release. For spore‐dispersed species, however, our knowledge is still very limited about the mechanisms triggering spore release and its relation to, for example, wind conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The dispersal ability of musk thistle is affected positively (larger growth) and negatively (higher precipitation lowers seed production) by climate change (Zhang et al 2011b). Marchetto et al (2012) suggested that musk thistle seed released during hot, dry conditions may increase plant invader fitness, potentially by increasing dispersal distances.…”
Section: )mentioning
confidence: 99%